Redox‐Active BIAN‐Based Iron Complexes in Catalysis. Issue 30 (22nd August 2022) - Chacon‐Teran, Miguel A.; Findlater, Michael
Abstract: α‐Diimine ligands have contributed extensively to the coordination chemistry of the majority of the transition metals; bis(arylimino)acenaphthene ligands (BIANs) have been widely studied and found to offer great versatility in their application as supporting ligands in catalytic transformations. In recent years, BIAN‐based iron complexes have proven effective in mediating a number of reductive transformations which includes hydrosilylation, hydroboration and hydrogenation chemistries. This review highlights the most recent contributions to the field. In our initial 2015 communication, we disclosed that the arene‐capped Fe(0) species Ar BIAN−Fe(toluene) mediates aldehyde and ketone hydrosilylation with exceptional activity under solvent‐free conditions. This led us to the discovery that such systems were capable of the hydrosilylation of imines and esters, the hydroboration of imines, aldehydes, ketones, alkenes, and alkynes and even the ring‐opening polymerization of rac ‐lactide. Spectroscopic and computational studies have firmly established the importance of redox non‐innocence in BIAN complexes and detailed mechanistic studies have revealed the importance of spin‐state‐crossing in catalysis. Although this work represents only a small component of advances in iron catalysis, our efforts have proven influential in Fe‐based approaches to reductive transformations and is likely to continue to inform the design of Fe‐based catalysts. Abstract : Iron has rapidly emerged as an attractive alternative to platinum group metals in catalysis. The key to unleashing iron's potential is its combination with appropriate ligand scaffolds. Bis(arylimino)acenaphthenes (BIANs) have recently found application as supporting ligands in iron‐based catalytic transformations. This review describes the most recent applications of iron‐BIANs in catalysis.